Plant biotechnological patents from the legal perspective - Abdullah, Farhah; Jusoff, Kamaruzaman (2009)
The purpose of this article is to examine the extent to which plant biotechnological patent in terms of natural product which has human intervention, different from other product and the entitlement of such a patent whether it is the inventor or biological donor’s patent? In addition, the article discusses how would one determine the “value” added” by the company’s researchers as opposed to the value contributed by the original genetic material. Meanwhile, the poor farmers and indigenous people who are the “pioneers” in terms of the knowledge of the plant, they are left unprivileged and deprived of their contribution and benefits. Thus, this article would highlight the significance of the contribution made by the original donor especially, in a poor developing country whose natural heritage has been “taken away” without any consideration, acknowledgment and how to strike a balance between the rights of an inventor and biological donor?